Deysi, gender, and violence - Liberato, Ana S. Q., 1970- author. Link
1 online resource (xviii, 212 pages)
Keywords: "This book shares the life narrative of Deysi Quiñones to shed light on the intricate relationship between her life and the wider cultural, political, social, and historical contexts of the Dominican Republic. Deysi's life narrative is a microhistory that sheds light on the intersection of gender, violence, and poverty under the Trujillo regime and in its wake. Her story recovers pieces of rural life, which has been disrupted, transformed, and made less visible by the neoliberal order. It emphasizes the significance of expanding the Trujillo regime archive to encompass a broader spectrum of perspectives and attract more scholarly attention to Petán Trujillo's legacies. Deysi's life story can provide meaningful lessons and insights for today in the realm of gendered violence and children's exploitation. This book is intended as reading for sociology, gender and women's studies, history, Latin American politics, and Caribbean and Latin American Studies courses and for a general educated audience. The book intersects with topics that are widely covered in research in the humanities and social sciences and is appropriate for both advanced undergraduate and graduate courses. The book can appeal to human rights activists, novelists, and individuals and organizations interested in history, politics, authoritarian societies, and gendered violence"--